SUSTAINABILITY ASSESSMENT OF AQUACULTURE AND FISHING COMMUNITIES IN DE GI LAGOON, BINH DINH PROVINCE - Tinh, Vo Thanh; Ly, Che Dinh (Vietnam Journal of Marine Science and Technology, 2014)
De Gi Lagoon is one of the large lagoon of Binh Dinh province. The study and evaluation on sustainability of the fishing and aquaculture communities around the lagoon show that the level of sustainable development is in medium level and there are many criteria with low-scores, including poor planning, no policy to support fishermen and sensitive effects of climate change.